2013
DOI: 10.1371/journal.pone.0079377
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electromagnetic Fields Improve Bone Microstructure and Strength in Ovariectomized Rats through a Wnt/Lrp5/β-Catenin Signaling-Associated Mechanism

Abstract: Growing evidence has demonstrated that pulsed electromagnetic field (PEMF), as an alternative noninvasive method, could promote remarkable in vivo and in vitro osteogenesis. However, the exact mechanism of PEMF on osteopenia/osteoporosis is still poorly understood, which further limits the extensive clinical application of PEMF. In the present study, the efficiency of PEMF on osteoporotic bone microarchitecture and bone quality together with its associated signaling pathway mechanisms was systematically invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 47 publications
(59 reference statements)
8
62
3
1
Order By: Relevance
“…As some treatments are defective, ineffective, expensive, low in patient compliance, and/or risky (as they disturb normal bone turnover physiology and/or cause significant side effects or even cancer), searching for alternative and effective therapies for osteoporosis is necessary and has been drawing attention of many clinicians and researchers [1,2]. While electromagnetic fields (EMFs) of extremely low frequency have been considered as a promising therapy for a wide range of bone diseases, such as fresh and nonunion fractures and osteoarthritis [3], accumulating evidence has now shown that pulsed electromagnetic fields (PEMFs) as an alternative noninvasive method were capable of producing satisfying therapeutic effects on osteoporosis [4]. PEMFs promote osteogenesis and mineralization of bone cells and prevent bone loss in animal models of disuse or tail-suspension osteoporosis and ovariectomy-induced bone loss [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As some treatments are defective, ineffective, expensive, low in patient compliance, and/or risky (as they disturb normal bone turnover physiology and/or cause significant side effects or even cancer), searching for alternative and effective therapies for osteoporosis is necessary and has been drawing attention of many clinicians and researchers [1,2]. While electromagnetic fields (EMFs) of extremely low frequency have been considered as a promising therapy for a wide range of bone diseases, such as fresh and nonunion fractures and osteoarthritis [3], accumulating evidence has now shown that pulsed electromagnetic fields (PEMFs) as an alternative noninvasive method were capable of producing satisfying therapeutic effects on osteoporosis [4]. PEMFs promote osteogenesis and mineralization of bone cells and prevent bone loss in animal models of disuse or tail-suspension osteoporosis and ovariectomy-induced bone loss [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the favorable effects of PEMFs on osteoporosis in OVX or hindlimb-suspended animals [6][7][8][9]. However, few studies have evaluated the effects of PEMFs on bone mass, bone microarchitecture, and bone strength together with their related signaling pathway mechanisms in animal models of diabetic osteopenia.…”
Section: Discussionmentioning
confidence: 99%
“…As a safe and noninvasive physiotherapy, pulsed electromagnetic fields (PEMFs) have been suggested as a promising treatment for diabetic osteopenia. It has been reported that PEMFs can increase bone mineral density (BMD) in osteoporosis patients [5], prevent bone loss in ovariectomy-induced osteoporosis rats [6][7][8] and hindlimb-suspended rats [9], improve bone formation [10,11], and inhibit bone resorption [12] in vitro. It has reported that the cellular functions of bone marrow stromal cell [13], osteoblast [14,15], and osteoclast [16,17] are abnormal under diabetic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the enhanced Wnt/β-catenin signaling induced by PEMFs notably elevated the expression of proliferation phase related target genes, Ccnd 1 and Ccne 1, and differentiation phase related genes, ALP, OCN, COL1, and Runx2, in osteoblast cells, which accelerated the osteoblasts proliferation, differentiation, and mineralization, three pivotal processes of bone formation [31, 32]. On the other hand, according to in vivo assay studies, PEMFs effectively reversed the bone mass loss and deterioration of bone microarchitecture analyzed by microCT and attenuated biomechanical strength deterioration evaluated by three-point bending test in hind limb-suspended ovariectomized rats through the Wnt/Lrp5/β-catenin signal pathway [33, 34], indicating that activating this pathway by PEMF exposure is beneficial for bone disorders.…”
Section: Underlying Signaling Pathwaysmentioning
confidence: 99%